Nurturing maternal health in the midst of difficult life circumstances: a qualitative study of women and providers connected to a community-based perinatal program - Maira Quintanilha; Maria J. Mayan; Kim D. Raine; Rhonda C. Bell (BMC, 2018)
Abstract Background Many socioecological and structural factors affect women's diets, physical activity, and her access and receptivity to perinatal care. We sought to explore women's and providers' perceptions and experiences of health in the pre- and post-natal period while facing difficult life circumstances, and accessing a community-based program partially funded by Canada Prenatal Nutrition Program (CPNP) in Alberta, Canada. Methods Following the principles of community-based participatory research, we conducted a focused ethnography that involved five focus groups with women (28 in total), eight one-on-one interviews with program providers, and observations of program activities. Data were analyzed through qualitative content analysis to inductively derive codes and categories. Results Women perceived eating healthy foods, taking prenatal vitamins, and being physically active as key health behaviours during pregnancy and postpartum. However, they were commonly coping with many difficult life circumstances, and faced health barriers for themselves and their babies. These barriers included pregnancy or birth complications, family and spousal issues, financial difficulties, and living rurally. On the other hand, women and providers identified many aspects of the community-based program that addressed the burden of adversities as enablers to better health during pregnancy and postpartum. Conclusion Community-based programs have an important role in alleviating some of the burden of coping with difficult life circumstances for women. With such potential, community-based programs need to be well supported through policies. Policies supporting these programs, and ensuring adequate funding, can enable more equitable services to rural women and truly promote maternal health during pregnancy and postpartum.